RETRACTED: Analysis Of Perceived Value Of Impulsive Buying With Attitudes And Beliefs As Mediator - Lily Purwianti; Keltine Richelle Chan (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
RETRACTED NOTICE Following up on the review of articles published in the Ekombis Review Journal carefully, carefully, and considering the article entitled " Analysis Of Perceived Value Of Impulsive Buying With Attitudes And Beliefs As Mediator" Vol 13 No 1 (2025), DOI: https://doi.org/10.37676/ekombis.v13i1.6699 This paper was found to violate the principles of the Ekombis Review Journal Publication and has been withdrawn. This article has been published in another journal and the article retraction letter is attached as a PDF. The document and its contents have been removed from the Ekombis Review Journal, and reasonable efforts should be made to remove all references to this article.